Identification of four novel genes contributing to familial elevated plasma HDL cholesterol in humans[S] - Roshni R. Singaraja; Ian Tietjen; G. Kees Hovingh; Patrick L. Franchini; Chris Radomski; Kenny Wong; Margaret vanHeek; Ioannis M. Stylianou; Linus Lin; Liangsu Wang; Lyndon Mitnaul; Brian Hubbard; et al. (Journal of Lipid Research, 2014)
While genetic determinants strongly influence HDL cholesterol (HDLc) levels, most genetic causes underlying variation in HDLc remain unknown. We aimed to identify novel rare mutations with large effects in candidate genes contributing to extreme HDLc in humans, utilizing family-based Mendelian genetics. We performed next-generation sequencing of 456 candidate HDLc-regulating genes in 200 unrelated probands with extremely low (≤10th percentile) or high (≥90th percentile) HDLc. Probands were excluded if known mutations existed in the established HDLc-regulating genes ABCA1, APOA1, LCAT, cholesteryl ester transfer protein (CETP), endothelial lipase (LIPG), and UDP-N-acetyl-α-D-galactosamine:polypeptide N-acetylgalactosaminyltransferase 2 (GALNT2). We identified 93 novel coding or splice-site variants in 72 candidate genes. Each variant was genotyped in the proband's family. Family-based association analyses were performed for variants with sufficient power to detect significance at P < 0.05 with a total of 627 family members being assessed. Mutations in the genes glucokinase regulatory protein (GCKR), RNase L (RNASEL), leukocyte immunoglobulin-like receptor 3 (LILRA3), and dynein axonemal heavy chain 10 (DNAH10) segregated with elevated HDLc levels in families, while no mutations associated with low HDLc. Taken together, we have identified mutations in four novel genes that may play a role in regulating HDLc levels in humans.